English in Australia - Blair, David, 1942-; Collins, Peter, 1950- (Varieties of English around the world. General series ;, 2001)
This unique collection fills a ten-year gap in studies on the nature of Australian English, and it is the first to deal exclusively with varieties of English on the Australian continent. The book contains chapters on the phonology, morphology, syntax and the lexicon of the dialect, and chapters on variation within the dialect that include Aboriginal and ethnic varieties as well as regional and generational differences with a focus on questions of Australian identity and intercultural relations. With selected contributions by Australia's leading linguists this volume records the most recent dev.